Implementasi Algoritma Gabor Wavelet Dalam Pengenalan Sketsa Wajah Pada Citra Digital - Tresia Dorarta Lumbantobing; Nel Astuti Hasibuan; Sumiati Adelina Hutabarat (JURIKOM (Jurnal Riset Komputer), 2021)
Until now, there have been many studies conducted on objects in the form of images, which are expected to be able to provide information, benefits and contributions to the development of better image processing, so as to increase new technological innovations. Talking about image processing, of course this cannot be separated from computer devices, therefore companies engaged in this field continue to spur their performance in improving the quality of making software that is better and can compete in the market and according to consumer demand. Image processing itself can be developed in many fields, where it is done to facilitate human work. One of them is in the field of art. Writing this study intends to use an object in the form of a facial sketch image to be processed using the Gabor Wavelet Algorithm in making the program, so that recognition of a person's face sketch can be carried out from the characteristics or details of the person's face sketch. In the world of art, facial sketches are common and many ordinary people can make them, because facial sketches do not require the creator to draw them perfectly, but can still show the details of a person's face sketched his face. The purpose of writing this research was carried out in order to facilitate the recognition of facial sketches, which until now rarely found research that discusses them. And the authors hope to assist in the development of better image processing in image recognition in the form of facial sketches